Health System Governance Capacity in Handling Stunting in South Bolaang Mongondow Regency - Mokodongan, Sadli (KnE Social Sciences, 2025)
Stunting is currently one of the most prevalent nutritional problems in Indonesia and has become the focus of an ongoing national intervention program. Stunting is a chronic nutritional problem caused by insufficient food intake over a relatively long period of time. A health governance system that can encourage a reduction in stunting rates is needed. This study aims to analyze the capacity of health system governance in handling stunting in South Bolaang Mongondow District. This research used a qualitative approach. Data collection methods include in-depth interviews, observation, and documentation. Data sources consist of primary data and secondary data. Informants in this study were local government officials at various related agencies, Posyandu cadres, village midwives, and village heads involved in handling stunting. Data analysis techniques include data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that the capacity of health system governance in handling stunting in South Bolaang Mongondow Regency is not fully adequate. This is because the human resources who play a role in handling stunting are not all trained in multidimensional stunting case management. Villages that are expected to allocate funds for handling stunting have not shown their commitment by implementing the stunting prevention program. The training provided has not been sustainable and equitable, in addition to limitations to its budget.